LITERATURE CITATION BY MEDICAL RESEARCHERS: A CITATION ANALYSIS OF THREE PAKISTANI MEDICAL JOURNALS - Ullah, Saeed; Jan, Saeed Ullah; Shah, Sabir; Butt, Najma Iqbal (Journal of Postgraduate Medical Institute, 2018)
Objectives: To analyze the citations of core Pakistani journals in the field of medical sciences; secondly it will provide an opportunity to provide access to the pattern of citations. Methodology: Three esteemed medical journals were selected for examination; namely Journal of the College of Physicians and Surgeons Pakistan (JCPSP), Pakistan Heart Journal (PHJ) and Pakistan Journal of Surgeons (PJS). It was decided to cover all the volumes and issues published in the last ten years (from 2007 to 2016). The content-wise analysis of citations included: authorship pattern of citation, citations per article, distribution of citations according to bibliographic forms, age of cited documents and a list of top most cited journals. Results: Pakistani journals were more frequently cited by these three reputed journals of medical field. Journal of Ayub Medical College (JAMC) was the most cited journal. In PHJ, most (27.71%) citations were three authored followed by four authored citations in JCPSP (27.17%). The frequency of citations up to 05 years old were PJS (33.34%), PHJ (30.28%) and JCPSP (29.99%). Furthermore, 90% citations were covered from journal sources. Conclusion: Majority of the authors cited Pakistani Journals, JAMC being the most cited journal. Most of the citations were covered from journal sources.